Meningkatkan Kemampuan Memilih Unsur Seni Rupa Melalui Metode Pemberian Tugas Pada SMP Negeri 2 Siak Hulu - Nursalmi, Nursalmi (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2017)
Students at the time of learning to make artworks have fears assigned to create works of art other than that too, the more severe is the fear at the time want to present the results of his work in the form of direct presentation in the classroom. It becomes a problem for the success of teachers in this case is the teacher who gives the teaching of cultural arts subjects. Through classroom action research, the result of applying the method of assigning tasks in order to improve the selection of art elements of students to make art in class IX in the arts and culture subjects was able to increase the choice of student art elements. Keywords: The ability to choose the art element, the method of assigning tasks